Agencias de consejo de votación (sobre la oportunidad de una convención internacional) - Ramírez Reyes, Santiago (2017)
Abstract: Proxy advisory firms are relatively new entities in the corporate landscape particularly in the general context of shareholders’ voting devices. Firms of the kind were established with the aim of assisting investors/shareholders with their expertise in how to vote their shares. These third-party consultants are not regulated by any government agency in most of the countries and not even required to disclose the methodology used to render their recommendations. The lack of accountability of proxy advisors but also the possible conflict of interests spotted in their activities have been constant concerns since the kinetic force of international commerce will certainly spread firms of the type all over the world. In this context it may be appropriate to start considering an international convention on the matter.